Simulation of the hybrid Tunka Advanced International Gamma-ray and Cosmic ray Astrophysics (TAIGA). (July 2015) - Kunnas, M; Astapov, I; Barbashina, N; Beregnev, S; Bogdanov, A; Bogorodskii, D; Boreyko, V; Brückner, M; Budnev, N; Chiavassa, A; Chvalaev, O; Dyachok, A; et al.
Abstract: Up to several 10s of TeV, Imaging Air Cherenkov Telescopes (IACTs) have proven to be the instruments of choice for GeV/TeV gamma-ray astronomy due to their good reconstrucion quality and gamma-hadron separation power. However, sensitive observations at and above 100 TeV require very large effective areas (10 km 2 and more), which is difficult and expensive to achieve. The alternative to IACTs are shower front sampling arrays (non-imaging technique or timing-arrays) with a large area and a wide field of view. Such experiments provide good core position, energy and angular resolution, but only poor gamma-hadron separation. Combining both experimental approaches, using the strengths of both techniques, could optimize the sensitivity to the highest energies. The TAIGA project plans to combine the non-imaging HiSCORE [8] array with small (∼10m 2 ) imaging telescopes. This paper covers simulation results of this hybrid approach.